Resistance training practices of Brazilian olympic sprint and jump coaches: Toward a deeper understanding of their choices and insights (Part III) - Loturco, I.; Zabaloy, S.; Pereira, L. A.; Moura, T. B. M. A.; Mercer, V. P.; Fernandes, V.; Zajac, A.; Matusinski, A.; Freitas, T.; Bishop, C. (Journal of Human Kinetics, 2024)
In the final part of this three-article collection on the training strategies of Brazilian Olympic sprint and jump coaches, we provide a detailed description of the resistance training methods and exercises most commonly employed by these speed experts. Always with the objective of maximizing the sprint and jump capabilities of their athletes, these experienced coaches primarily utilize variable, eccentric, concentric, machine-based, isometric, complex, and isoinertial resistance training methods in their daily practices. Squats (in their different forms), Olympic weightlifting, ballistics, hip thrusts, lunges, calf raises, core exercises, leg curls, stiff-leg deadlifts, and leg extension are the most commonly prescribed exercises in their training programs, during both the preparatory and competitive periods. Therefore, the current manuscript comprehensively describes and examines these methods, with the additional aim of extrapolating their application to other sports, especially those where sprint speed is a key performance factor.